Effect of Nicotinic Acid on Fresh Semen Characteristics in Miniature Pigs - Yeon-Ju Lee; Sang-Hee Lee; Eunsong Lee; Seung Tae Lee; Hee-Tae Cheong; Boo-Keun Yang; Seunghyung Lee; Choon-Keun Park (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Objective of this study was to investigate the effect of nicotinic acid (NA) on the characteristics in fresh semen of miniature pig. We evaluated viability, acrosome reaction and mitochondrial integrity of sperm on 0, 3, 7 and 10 days during storage period with nicotinic acid. As results, the survival rate of sperm in 15 mM NA (day 3, 87.8 ± 1.2%; day 5, 84.0 ± 2.7%; day 7, 82.2 ± 0.9%) and 30 mM NA (day 3, 87.7 ± 0.3%; day 5, 84.4 ± 2.5%; day 7, 82.3 ± 0.7%) groups were higher than control and 5 mM NA groups in 3, 7 and 10 days of semen storage. The NA-treated sperm on 10 day was used day for observing acrosome integrity. The survival sperm with acrosome reaction was higher in 30 mM NA group (day 3, 2.7 ± 0.2%; day 5, 3.3 ± 0.6%; day 7, 11.4 ± 0.3%) than in the control, significantly (P<0.05). Moreover, the live sperm with mitochondrial integrity was higher in whole treatment groups of NA than control group, significantly (P<0.05). Specially, most mitochondrial integrity on 10 day of semen storage was significantly higher in 30 mM NA group (90.2 ± 1.6%) than other treatment groups (control, 81.8 ± 3.1%; 5 mM NA, 83.4 ± 3.0%; 15 mM NA, 89.1 ± 0.7%, P<0.05). In conclusion, supplement of NA in liquid semen of miniature pig can improve and maintain semen quality, such as viability, acrosome reaction, and mitochondria integrity.